A modified framework for the regional assessment of climate and human impacts on net primary productivity. (January 2016) - Pan, Ying; Yu, Chengqun; Zhang, Xianzhou; Chen, Baoxiong; Wu, Junxi; Tu, Yanli; Miao, Yanjun; Luo, Liming
Highlights: HANPP framework was modified for regional applications. NPPgap was introduced as NPPpot minus the sum of NPPeco and HANPP. NPPgap depicted errors in NPP components estimations. No considering of precipitation legacy and compensatory growth caused NPPgap . Fluctuation levels of NPPgap reflected the stability of vegetation productivity. Abstract: Improving models that depict the components of net primary production (NPP) in ecosystems will help us to better understand how climate change and human activities affect the biosphere. In this study, NPPgap was introduced into the present human appropriation of net primary production (HANPP) framework. We introduced NPPgap in this study as potential NPP (NPPpot ) minus the sum of ecosystem NPP (NPPeco ) and HANPP, which relates to the ability of models to depict NPP components. Using the Lhasa River region of the Tibetan Plateau, we examined temporal and spatial variations in the components of NPP over a 10-year period. Results showed that NPPpot, HANPP and NPPeco increased from 2000 to 2010, but at different rates and with different spatial patterns. NPPgap each year ranged from −9.2% to 13.1% for each site and on average composed 1.2% of the total NPPpot . NPPgap was significantly correlated with precipitation, plant biodiversity, plant height and soil properties. NPPgap increased if either of the previous 2 years had been wet years with relative high precipitation. An increase in the richness of palatable species would lead to a larger NPPgap through more compensatory growth. The large fluctuation level of NPPgap reflected the higher stability of vegetation productivity, which is caused by higher plant heights and soil maximum water capacity. This study showed the potential of the HANPP framework in regional assessment of climate and human impacts on net primary productivity. The use of the NPPgap measure reflects the gap in our knowledge and our ability to accurately estimate the components of NPP.